Disturbance Effects on Soil Carbon and Greenhouse Gas Emissions in Forest Ecosystems - Cai, Yanjiang (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Forest ecosystems are often disturbed by agents such as harvesting, fire, wind, insects and diseases, and acid deposition, with differing intensities and frequencies. Such disturbances can markedly affect the amount, form, and stability of soil organic carbon in, and the emission of greenhouse gases, including CO2, CH4, and N2O from, forest ecosystems. It is vitally important that we improve our understanding of the impact of different disturbance regimes on forest soil carbon dynamics and greenhouse gas emissions to guide our future research, forest management practices, and policy development. This Special Issue provides an important update on the disturbance effects on soil carbon and greenhouse gas emissions in forest ecosystems in different climate regions.